2015
DOI: 10.1155/2015/427038
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Synthesis and Roles of Hyaluronan in Peritoneal Dialysis

Abstract: Hyaluronan (HA) is a ubiquitous extracellular matrix glycosaminoglycan composed of repeated disaccharide units of alternating D-glucuronic acid and D-N-acetylglucosamine residues linked via alternating β-1,4 and β-1,3 glycosidic bonds. HA is synthesized in humans by HA synthase (HAS) enzymes 1, 2, and 3, which are encoded by the corresponding HAS genes. Previous in vitro studies have shown characteristic changes in HAS expression and increased HA synthesis in response to wounding and proinflammatory cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 124 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…This effect was confirmed, for example, in dermal, cardiac, lung, renal, and liver fibrosis 21,29–33 . As was reviewed in our previous study, 14 with respect to the peritoneal cavity, there are just a few studies focused on the role of endogenous HA in the regulation of ECM deposition and accompanying processes, most of them concerning the disruption of peritoneal membrane homeostasis during peritoneal dialysis 50 . Raby et al reported that a higher production of HA during peritoneal dialysis contributes to inflammation and fibrosis through the action TLR2 on MCs and the phosphorylation of ERK 38 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This effect was confirmed, for example, in dermal, cardiac, lung, renal, and liver fibrosis 21,29–33 . As was reviewed in our previous study, 14 with respect to the peritoneal cavity, there are just a few studies focused on the role of endogenous HA in the regulation of ECM deposition and accompanying processes, most of them concerning the disruption of peritoneal membrane homeostasis during peritoneal dialysis 50 . Raby et al reported that a higher production of HA during peritoneal dialysis contributes to inflammation and fibrosis through the action TLR2 on MCs and the phosphorylation of ERK 38 .…”
Section: Discussionmentioning
confidence: 53%
“…21,[29][30][31][32][33] As was reviewed in our previous study, 14 with respect to the peritoneal cavity, there are just a few studies focused on the role of endogenous HA in the regulation of ECM deposition and accompanying processes, most of them concerning the disruption of peritoneal membrane homeostasis during peritoneal dialysis. 50 Raby et al reported that a higher production of HA during peritoneal dialysis contributes to inflammation and fibrosis through the action TLR2 on MCs and the phosphorylation of ERK. 38 During endometriosis, which can also lead to the development of adhesions, the importance of peritoneal MC-derived HA in the adherence of endometrial cells to the mesothelial monolayer was also proven.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated HA in serum in the presence of impaired liver function is informative in predicting liver fibrosis. In recent studies on rat models and PD patients, HA has been used as a biomarker for monitoring PD progression, elevated serum HA levels have been shown to predict mortality and morbidity within 18 months in PD patients [ 51 ]. But more multi‐center and larger sample size studies should be conducted afterward to further corroborate.…”
Section: Other Novel Parametersmentioning
confidence: 99%